Isolation of Neoparamoeba pemaquidensis Page, 1987 from Marine and Estuarine Sediments in Tasmania - Crosbie, PBB; Barbara Nowak; Carson, J (2003)
To gauge environmental ubiquity of Neoparamoeba pemaquidensis, the causative agent of amoebic gill disease (AGD) in farmed Atlantic salmon in Tasmania, sediments in both marine and estuarine sites, including those with no history of AGD, were screened for presence of the organism. With one exception N. pemaquidensis was detected in all locations.